Anti-windup design for networked time-delay systems subject to saturating actuators under round-robin protocol - Chen, Yonggang; Zhao, Yaxue; Gu, Zhou; Yang, Xinfen (Applied mathematics and computation, 2025)
This paper investigates the anti-windup design for networked time-delay systems subject to saturating actuators under the round-robin protocol. Firstly, the actual measurement output is represented by the model that is dependent on a periodic function. Then, using the generalized delay-dependent sector condition, the augmented periodic Lyapunov-Krasovskii functional together with certain inequalities, an anti-windup design criterion is derived based on linear matrix inequalities under which the closed-loop systems have the desirable properties such as boundedness, H∞ performance, and asymptotic stability. The corresponding results are also presented for the case of constant delay and the case of no time delay. Moreover, the relevant optimizations in the main results are discussed. In the end, two numerical examples illustrate the availability and advantages of the proposed results. •Anti-windup design criteria are obtained for networked systems with state delay and actuator constraints under the round-robin protocol.•Delay-dependent sector conditions are proposed to reduce the inherent conservatism of the obtained results.•Augmented periodic Lyapunov-Krasovskii functionals are constructed to analyze the closed-loop systems in a less conservative way.